2003
DOI: 10.2519/jospt.2003.33.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Quality of Randomized Controlled Trials for Patellofemoral Pain Syndrome

Abstract: 4Study Design: Systematic review of the literature. Objectives: To develop a grading scale to judge the quality of randomized clinical trials (RCTs) and conduct a systematic review of the published RCTs that assess nonoperative treatments for patellofemoral pain syndrome (PFPS). Background: Systematic reviews of the quality and usefulness of clinical trials allow for efficient synthesis and dissemination of the literature, which should facilitate clinicians' efforts to incorporate principles of evidence-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 68 publications
0
71
1
4
Order By: Relevance
“…Despite this, many review and concept articles continue to highlight quadriceps strengthening as an important intervention for patients with PFPS. 3,23,44 Limited research on the efficacy of isolated hip strengthening has provided evidence of improvements in pain, function, and strength in this population. 31,34 The presence of multiple effective interventions creates a dilemma for clinicians treating patients with PFPS.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Despite this, many review and concept articles continue to highlight quadriceps strengthening as an important intervention for patients with PFPS. 3,23,44 Limited research on the efficacy of isolated hip strengthening has provided evidence of improvements in pain, function, and strength in this population. 31,34 The presence of multiple effective interventions creates a dilemma for clinicians treating patients with PFPS.…”
Section: T T Conclusionmentioning
confidence: 99%
“…The following databases were used by the 10 included reviews: MEDLINE, 2,9,12,20,23,37,41,60,70 EM-BASE, 12,41,70 SPORTDISCUS, 2,12,70 CI-NAHL, 2,9,12,20,23,37,41,70 Web of Science, 9 Cochrane Database of Systematic Reviews, 9 Cochrane, 12,23,41,70 HealthSTAR, 12 PEDro, 12,20,41,70 Current Contents, 12,20 Biological Abstract databases, 37 Pubmed (clinical queries component), 37 AMED, 60,70 EBSCO Health Databases (limits clinical trial), 60 Cochrane Musculoskeletal Injuries Group, 41 Cochrane Rehabilitation and Related Therapies Field specialized registers, 41 Cochrane Controlled Trials Register, 41,70 Cochrane Library Reviews, 70 and Cochrane Library Protocols. 70 Inclusion/exclusion criteria used in the systematic reviews can be found in …”
Section: Methodology Summary For Included Reviewsmentioning
confidence: 99%
“…Incidence rates are even more pronounced among sports enthusiasts, accounting for up to 40% of injuries in sports medicine (6).…”
Section: Introductionmentioning
confidence: 99%